ANALISIS PENGARUH MODAL KERJA TERHADAP KEMAMPULABAAN PADA TOKO MAZAYYA - Nur Fatma; Ahmad Tomu (JURNAL ULET (Utility, Earning and Tax), 2020)
To achieve the company’s goal, namely increasing firm value by maximizing profitability, there are various factors that affect the level of profitability. Therefore, this study aims to determine the effect value of cash turnover, accounts receivable turnover and inventory turnover on profitability at Mazayya’s Store during 2015-2018.This study uses an associative method to describe the influence relationship between variables with multiple linear regression analysis instruments. The research data were collected using observation, interview, and documentation techniques. The results showed that the variable cash turnover and accounts receivable turnover did not have a significant effect on profitability at Mazayya's Stores, while the inventory turnover variables had a significant effect on profitability at Mazayya's Stores.